Microbial Community Rearrangements in Power-to-Biomethane Reactors Employing Mesophilic Biogas Digestate - Ács, Norbert; Szuhaj, Márk; Wirth, Roland; Bagi, Zoltán; Maróti, Gergely; Rákhely, Gábor; Kovács, Kornél L. (Frontiers in Energy Research, 2019)
The biological conversion of hydrogen (H2) and carbon dioxide (CO2) to methane (CH4), is accomplished by the hydrogenotrophic methanogens (HM). HMs are difficult to cultivate in pure culture, but they are readily available in the mixed culture of effluents from the anaerobic degradation of organic matter, i.e. the fermentation effluent of biogas plants. The rate-limiting step in the work of CH4-forming microbial communities is the low solubility of H2 in the aqueous environment. In our approach, the simple fed-batch fermentation technique was selected to supply the gaseous substrates for the microbial community at laboratory scale and mesophilic temperature. Periodically withdrawn samples were analyzed for process parameters and the microbial communities were studied using Terminal Restriction Fragment Length Polymorphism (T-RFLP) of the mcrA gene and Ion Torrent whole metagenome DNA sequencing. The metagenome data were evaluated by both read-based and genome-centric bioinformatics tools. The rearrangements in the mixed microbial communities, triggered by switching the operating conditions to biological power-to-biomethane (bio-P2M), have been established. The production rates were 6.30 mL CH4 L-1 h-1 during the acclimation phase and 9.21 mL CH4 L-1 h-1 by the fully adapted community, respectively. The diversity of the anaerobic microbiota decreased as the bio-P2M process progressed. Feeding the community with H2 apparently promoted the abundance of several genera, in particular Candidatus Cloacimonas and Herbinix. The diversity of the Archaea community decreased considerably upon daily feeding with H2 and CO2. The predominant Archea genus was Methanobacterium in every reactor, Methanothrix persisted for the first 4 weeks, while the initially less abundant genus Methanoculleus gained advantage during the adaptation to the sustained bio-P2M process. The accumulation of acetate indicated a strong involvement of homoacetogenic bacteria.